Pneumatic Dilation in Geriatric Achalasia Patients - Tenlik, İlyas and Öztürk, Ömer and Özin, Yasemin and Arı, Derya and Coşkun, Orhan and Turan Gökçe, Dilara and Gökbulut, Volkan and Göktaş, Zeynep and Kılıç, Zeki Mesut Yalın (Turkish Journal of Gastroenterology, 2023)
Background: The aim of the study was to share the effectiveness of pneumatic dilation in geriatric achalasia patients. Methods: Achalasia patients over the age of 65 and those under the age of 65 as the control group who received pneumatic dilation as the first-line treatment were evaluated in the study. Results: The average age of geriatric patients was 72.5 ± 55.92 years (65-90), with 50.3% of them being male. Follow-up was conducted for a mean of 64.52 ± 38.73 months. While pneumatic dilation was successful in 98.6% (141/143) of geriatric patients, it was also successful in 94% (141/150) of non-geriatric patients. Remission after single balloon dilatation was observed in 81.8% of geriatric patients, while it was observed in only 52.7% of non-geriatric patients (P = .000). When comparing remission after single dilatation and multiple dilatations, it was observed that geriatric patients who achieved remission after multiple balloon dilatation had higher lower esophageal sphincter pressure and Eckardt scores at the diagnosis and higher lower esophageal sphincter pressure and esophageal body resting pressures after the first balloon dilatation. Conclusions: The proportion of elders in the world population is increasing daily and this disease has been known to disproportionately afflict this group. Although surgical treatments, in particular per-oral endoscopic myotomy, have recently gained popularity as therapies for achalasia, pneumatic dilation remains the most commonly used in geriatric patients. Cite this article as: Tenlik İ, Öztürk Ö, Özin Y, et al. Pneumatic dilation in geriatric achalasia patients. Turk J Gastroenterol. 2023;34(4):332-338.